Pachjiri. Cerro sagrado del Titicaca - Fernández Juárez, Gerardo; Albó Corrons, Xavier (Revista Española de Antropología Americana, 2008)
This paper describe the ethnographic characteristics of mountain called Pachjiri and his ceremonial altars, which make him a sacred place for the Aymara communities near to Titicaca lake. The mountain is sacred in a double sense: as center for the initiation of Aymara ritual specialists (yatiris), and as place of peregrination during August, for sacrificing offers in his different ritual altars. Recently, the Aymara «hermanos protestantes» (protestants believers) are started a symbolic fight on the ceremonial place, specially after the murmurs of a human sacrify to the mountain.
Keywords: Pachjiri; Aymara; Yatiri; Bolivia